The diagnostic value of the droplet digital PCR for the detection of bovine deltapapillomavirus in goats by liquid biopsy. Issue 6 (29th January 2021) - Cutarelli, Anna; De Falco, Francesca; Uleri, Valeria; Buonavoglia, Canio; Roperto, Sante
Abstract: In the present study, the highly pathogenic bovine deltapapillomavirus (δPV) was investigated by liquid biopsy in blood samples of 168 clinically normal goats using both droplet digital PCR (ddPCR) and quantitative real‐time PCR (qPCR). Overall, ddPCR discovered BPV E5 DNA in ~ 61.3% of the blood samples examined, while real‐time qPCR revealed the virus in ~ 10.7% of the same samples. Moreover, ddPCR showed BPV E5 DNA in ~ 78.8% of blood samples from goats that were in close contact with cattle and in 20% of blood samples from goats living in closed pens without any contact with cattle. In addition, ddPCR unmasked a single BPV genotype in ~ 59.2% and multiple genotypes in ~ 40.8% of goats harbouring BPV DNA, while real‐time qPCR detected single genotypes in ~ 17% and multiple genotypes in ~ 1%. Of the BPV co‐infections detected by ddPCR, 28 (~67%) involved two genotypes, eight (~19%) three genotypes and six (~14%) four genotypes. In contrast, real‐time qPCR revealed BPV co‐infection by two genotypes in only one sample and failed to detect co‐infection by three or four genotypes. BPV2 and BPV13 were the most prevalent viruses responsible for single and multiple co‐infections, respectively. The present study showed that ddPCR is promising method for circulating bovine papillomavirus DNA detection and quantification and suggested that animal husbandry practices contribute to cross‐species transmission of BPVs.